Upaya Meningkatkan Kemampuan Memakai Sepatu Bertali Melalui Analisis Tugas pada Mata Pelajaran Bina Diri Pada Anak Tunagrahita Ringan Kelas II di SLB Asuhan Kasih Kota Kupang - Nggadi, Intan May; Selan, Ot Bil Wilson; Wangge, Vinsesnsius; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the ability of mildly intellectually disabled children in Grade II at SLB Asuhan Kasih, Kupang City, to wear lace-up shoes through Task Analysis in the Personal Development subject. Children with special needs are entitled to education, including the development of self-help skills, self-care, and self-management. Observation results indicated that mildly intellectually disabled students faced difficulties in wearing lace-up shoes, particularly in understanding the steps and coordinating hand movements. This Classroom Action Research (CAR) involved 3 Grade II students (MRR, PPJ, PVS). The results of Cycle II showed a significant improvement, where all subjects reached the Very Good category (scores 85-95), after previously being in the Very Poor category (scores 30-40) during the pre-test. The conclusion of this study is that the use of lace-up shoe media can enhance students' ability and concentration in wearing lace-up shoes